C3 glomerulonephritis with genetically confirmed C3 deficiency in a pediatric patient: a case report - Hae Min Kim; Jae Il Shin; Ji Hong Kim; Jiyoung Oh; Ji-Man Kang; Hee Gyung Kang; Seong Heon Kim; Byoung Soo Cho; Keum Hwa Lee (Korean Society of Pediatric Nephrology, 2024)
Complement component 3 glomerulonephritis (C3GN) is a rare kidney disease characterized by complement dysregulation that results in prominent complement component 3 (C3) deposition in the kidneys. The clinical course of C3GN varies from mild hematuria to progressive chronic kidney disease. In most patients, C3GN is driven by acquired factors, namely, autoantibodies that target C3 or C5 convertases. Genetic variations in complement-related genes are less frequent. We report the case of a 9-year-old Korean boy who presented with microscopic hematuria and a persistently low C3 level and had biopsy findings of C3GN, with the presence of a C3 gene mutation: a frameshift mutation associated with C3 deficiency. However, the patient did not exhibit any other symptoms of complement deficiency. Direct DNA sequencing of his family members revealed the same genetic mutation in his father and older brother. This case report is significant because there are very few such reports worldwide concerning gene mutations related to C3 deficiency to be discovered in patients with C3GN. Explaining C3GN pathogenesis is challenging; therefore, additional research is required in the future.